(untitled) (Acta Scientiarum. Animal Sciences, 2018)
Transportation of live fish is routinely done in aquaculture; therefore, the aim of this study was to analyze the water quality and survival rate of Rhamdia quelen fry (2.55±0.44 g) following 4, 8 and 12h of simulated transportation, at stock densities of 30 and 60 fry 5 L-1 and temperatures 15, 20 and 25oC. Dissolved oxygen, pH, electrical conductivity, total ammonia, nitrite, nitrate, turbidity, total alkalinity and survival were analyzed. Temperature and time had a significant influence on ammonia, pH, electrical conductivity, and dissolved oxygen levels, and fish died after 12 hours of transportation simulation when kept at 20 and 25ºC. The density directly affected the water quality parameters, such as the increase in electrical conductivity and turbidity, and decrease in dissolved oxygen and pH at the density of 60 fish 5 L-1. In conclusion, the transportation of R. quelen fry should be carried out at temperatures between 15 and 25°C, for periods of less than 12 hours, and at stock density of up to 6 fish per liter of water so as not to impair the homeostasis of the fry, and consequently, their survival.